Pinduoduo: Raising an 824 million-strong E-commerce empire under six years - TULI, Kapil R. (Institutional Knowledge at Singapore Management University, 2022)
At 824 million, Pinduoduo had the most customers in global e-commerce as of March 2021. It had also expanded aggressively into grocery shopping with Duo Duo Grocery, riding on the demands that emerged during the COVID-19 pandemic, and set its sights on becoming the world’s grocer. Despite its formidable progress, the e-commerce platform remained in the red, recording a loss of more than US$443 million in the first quarter of 2021. Its closest rivals, Alibaba and JD, remained hot on its heels, matching its forays into its stronghold of the lower-tier cities in the country. The year 2021 also marked a year of leadership renewal for Pinduoduo. Colin Zheng Huang, its founding CEO and Chairman, had passed the baton of leadership to Lei Chen, a fellow co-founder. Huang’s decision to step aside was to focus on figuring out the future of Pinduoduo. He believed research on food and life sciences would remake agriculture in China. How should investors see these moves and achievements by Pinduoduo? Are farming and smart logistics its ‘end game’? This case is more suitable for senior undergraduate and graduate classes. Students could learn about (1) the patterns of growth that organisations experience and their respective strategies; (2) the market positions that organisations assume and their accompanying strategies; (3) components of a marketing strategy (e.g., segmentation, targeting, positioning) and their respective strengths and weaknesses; and assessing the value propositions and sustainability behind a firm’s marketing strategy.